PENGARUH CONTENT MARKETING PADA GENERASI DIGITAL NATIVE TERHADAP CUSTOMER ENGAGEMENT DI MEDIA SOSIAL : KAJIAN SYSTEMATIC LITERATURE REVIEW - Siti Lamsiah Badrusalam Mahfud; Gibson Manalu (CV. Denasya Smart Publisher, 2025)
The swift advancement of digital technology and marketing has been profoundly altered by social media strategies, especially in relation to engaging the digital native generation. swift advancement of digital technology and Marketing has been profoundly altered by social media strategies, especially in relation to engaging the digital native generation Marketing has been profoundly altered by social media strategies, especially in relation to engaging the digital native generation. Marketing practices, particularly renf on marketing on customer engagement across Instagram and TikTok, are just two of the social media platforms involved. The findings consistently demonstrate that, through the use of strategic, relevant, and attractive content, content marketing positively affects customer engagement, with measured contributions ranging from 42.5% to 78.4%. The reviewed studies employed various quantitative methods, including surveys, simple linear regression, ANOVA, and correlation analysis. The studies cover a range of industries, including food and beverage, beauty, e-commerce, and education. This shows that customer engagement is driven not only by the quantity of content as the determining factor but also by its quality, interactivity, and emotional resonance. This review emphasises the vital role of content marketing in cultivating stronger customer relationships, brand loyalty, and, consequently, business growth within the digital landscape.